Development of Village Ecotourism in Sindangkasih Tourism Village Based on Tourism Satisfaction and Preference in Garut Regency - Asri, Shafitri Rahma Dani; Untari, Rini; Resmayasari, Ira (Program Studi Pariwisata, UPN Veteran Jawa Timur, 2023)
Tourist visits are an important aspect of maintaining the existence of tourist destinations, including in the Garut Regency area. This district has great potential in developing village ecotourism. Sindangkasih Tourism Village, one of the tourist villages in Garut Regency, has great potential for developing village ecotourism. The research aims to identify ecotourism resources and identify tourist satisfaction and preferences using a questionnaire with a Likert scale of 1-7 from 30 tourist respondents. Data collection was carried out over three months, from April to June 2022. wild fauna as well as the seven elements of culture. The results of the tourist assessment regarding satisfaction with the highest score on natural attractions, namely river landscapes and natural scenery, and cultural attractions, namely art. Tourists rate very satisfied with transportation to tourist villages and tourist routes. Tourists at a general rate are satisfied with the facilities and infrastructure in the village, besides that they are very satisfied with the tourism activities carried out at the Ngagogo pond, playing in the river and enjoying the natural scenery. The highest preference for tourism activities is enjoying natural scenery and playing traditional games during holidays taking into account the existence of the attractions provided.